Output-Based Aid in Morocco (Part 1) : Extending Water Services to the Poor in Urban Areas - Beauchêne, Xavier Chauvot de (World Bank, Washington, DC, 2012)
Morocco is a middle-income country with good water infrastructure that provides access to safe drinking water and sanitation to the majority of the urban population. In 2005, Morocco made it a priority to extend service to poor peri-urban settlements, and encouraged operators and local governments to reduce connection fees for their inhabitants. These connection fees had been priced at marginal cost, which represented a major obstacle for poor populations to connect to piped service. The government and the operators of water utilities in Casablanca, Meknes, and Tangiers consequently requested a grant from the Global Partnership on Output-Based Aid (GPOBA) to pilot the introduction of performance-based subsidies to encourage service expansion under an innovative output-based aid (OBA) approach. Initial results show that this approach is helping to refocus service provision on household demand, which has increased accountability, strengthened partnerships between local authorities and operators, and made monitoring of service delivery a priority. The World Bank is now working with the government to plan a scale-up program.